THE SPIRITUAL SYMBOLS IN BILLIE EILIS’S LYRIC SONGS - S, Ulfani; Nur, Riola Haya; Ahmad, Ardiansyah (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
This research analyze the Spiritual Symbols in Billie Eilish's Lyric Songs. Undergraduate Thesis for Sarjana Sastra Degree, English Department, Faculty of Letters, Universitas Muhammadiyah Purwokerto. This research focuses on spiritual symbols in Billie Eilish’s lyric songs. These lyric songs were chosen because they contained the issues of the spiritual symbols in Billie Eilish's lyric songs. The data were analysed by using semiotic theory by Roland Barthes and Ernst Cassirer. The primary data were taken from the music videos and the lyrics. Meanwhile, the secondary data were taken from the books, journals, and articles. From this analysis, it is found that there are symbols that tend to present the idea of Spiritual in relation to the evidence contained in the results of the analysis. Satanism was found in Billie Eilish's lyric songs.